Emotion detection in text data: a comparative study of machine learning algorithms - Hayatu, Ikrama Dayyabu; Singh, Sachin; Muhammad, Mustapha Mukhtar; Mishra, Rohan; Mishra, Manish (Brazilian Journal of Biometrics, 2025)
Emotion detection plays a vital role in understanding human sentiments and behaviors across various applications, including customer feedback analysis and mental health monitoring. This research assesses the efficiency of different algorithms for machine learning in detecting emotions in text data. A meticulously curated dataset is utilized for the study. The research compares conventional models like Logistic Regression (LR), Random Forest (RF), Support Vector Machines (SVM), and Naive Bayes (NB) with deep learning models like Long Short-Term Memory (LSTM), Convolutional Neural Networks (CNN), and Bidirectional Encoder Representations from Transformers (BERT). The performance of each algorithm is assessed using accuracy, precision, recall, and F1 score. BERT exhibits superiority over other models, achieving the maximum accuracy of 0.8867 and F1 Score of 0.8871. CNN and SVM also display commendable performance. While the traditional models perform adequately, they are surpassed by deep learning models, with Naive Bayes showing the lowest metrics. This study underscores the significance of selecting models based on specific application requirements, taking into account factors like interpretability and efficiency. Future research endeavors may explore multimodal approaches, model interpretability, bias reduction, and real-time applications, thereby contributing to the advancement of emotion detection in text.